INTERPLAY BETWEEN DISORDER AND ELECTRON INTERACTIONS IN A D=3 SITE-DISORDERED ANDERSON-HUBBARD MODEL - A NUMERICAL MEAN-FIELD STUDY - Tusch, M; Logan, D (1993)
We consider a numerical mean-field study, at the unrestricted Hartree-Fock level, of a Gaussian site-disordered Anderson-Hubbard model on a simple cubic lattice. The phase diagram at half filling is obtained, including magnetic and metallic-insulating phases, and all relevant phase boundaries are found to occur in a relatively weak-coupling regime. Variation with filling fraction y is also considered, with particular reference to the y-differential disorder-induced enhancement of electron interactions that lead to site-differential local-moment formation. The inhomogeneous distribution of local charges and magnetic moments over the sites is found to influence strongly the distribution and character of pseudoparticle states. This enables a simple microscopic rationalization of the metal-insulator transition and its phase boundaries in terms of an interplay between disorder and electron interactions, giving in addition a natural explanation for the two-fluid-like coexistence of delocalized charge-carrying states and strong-local-moment sites. © 1993 The American Physical Society.